Assessment of Effect of Magnesium Intake on Blood Pressure Control in Hypertensives: A Case-control Study with a Nested Intervention of Flax Seeds Administration to Increase Magnesium Intake - Vidhi Patel; Ashutosh Chauhan; Shubhangi Deshpande; Lalithambigai Arumugasamy; Nishi Patel (Indian Journal of Medical Biochemistry)
Aim and background: A significant proportion of hypertensive patients do not achieve good blood pressure (BP) control despite optimal medications and salt restriction. Considering the BP-lowering effect of magnesium reported in some previous studies, we wanted to assess the correlation between magnesium intake and control of BP in Indian hypertensives. Twenty-four-hour urinary magnesium excretion was used as a surrogate marker of magnesium intake. Further, the effect of supplementation of magnesium-rich flaxseeds on control of BP was assessed, in a subset of the study subjects. Methodology: In this case-control study, 40 patients of essential hypertension with poor BP control as per JNC-8 BP goals were enrolled as cases and 40 patients of essential hypertension with good BP control were enrolled as controls. Twenty-four-hour urinary samples were collected in both cases and controls and urinary magnesium-creatinine (Mg/Cr) ratios were estimated. The urinary Mg/Cr ratios of patients of the two groups were compared using the Mann–Whitney U test. A subset of 23 patients was given an intervention of three tablespoons of roasted whole flaxseeds daily for 4 weeks, and the significance of the change in mean BP, before and after the intervention, was assessed using a paired t-test. Results: The urinary Mg/Cr ratio in the good BP-control group [median = 77.05 [interquartile range (IQR)] = 23.51–101.80] was higher, compared to the poor BP-control group [median = 56.49 (IQR = 44.19–69.97)], with p-value = 0.02852, when tested with Mann–Whitney U test. In the subset of consenting participants, who took 3 Tbsp flax seeds daily, the average systolic BP and diastolic BP decreased significantly, from 141.13 (SD = 11) mm Hg and 87.65 (SD = 9.19) mm Hg to 134.22 (SD = 11.50) mm Hg and 84.65 (SD = 8.17) mm Hg, respectively (Paired t-test; p-value for SBP = 0.005, DBP = 0.013). Conclusion: Hypertensive patients with good BP control have higher levels of 24-hour urinary magnesium excretion when compared to patients with poor BP control. Flaxseeds can be used in hypertensive patients as an adjuvant to drug therapy to improve BP control. Clinical significance: Hypertensive patients can be advised to consume flax seeds regularly to maintain healthy magnesium levels and control hypertension.